2016
DOI: 10.1074/jbc.m116.754028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Scaffold-induced Linear Ubiquitinylation of B Cell Lymphoma/Leukemia 10 (Bcl10) during T Cell Receptor and Oncogenic Caspase Recruitment Domain-containing Protein 11 (CARD11) Signaling

Abstract: Edited by Eric FearonThe activation of NF-B downstream of T cell receptor (TCR) engagement is a key signaling step required for normal lymphocyte function during the adaptive immune response. During TCR signaling, the adaptor protein Bcl10 is inducibly recruited to the CARD11 scaffold protein as part of a multicomponent complex that induces IB kinase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 58 publications
(95 reference statements)
2
83
0
Order By: Relevance
“…Genetic studies demonstrated that defects in LUBAC components attenuate TNF␣-induced NF-B activation and gene expression (18 -20). In addition to TNF␣, LUBAC regulates interleukin-1, CD40-, lymphotoxin ␤-, Toll-like receptor-, T cell receptor-, and nucleotide-binding oligomerization domain containing 2 (NOD2)-mediated cellular events through regulating the NF-B pathway (21)(22)(23). Recent studies reported M1-linked ubiquitination to have an NF-B-independent function as well (24,25).…”
mentioning
confidence: 99%
“…Genetic studies demonstrated that defects in LUBAC components attenuate TNF␣-induced NF-B activation and gene expression (18 -20). In addition to TNF␣, LUBAC regulates interleukin-1, CD40-, lymphotoxin ␤-, Toll-like receptor-, T cell receptor-, and nucleotide-binding oligomerization domain containing 2 (NOD2)-mediated cellular events through regulating the NF-B pathway (21)(22)(23). Recent studies reported M1-linked ubiquitination to have an NF-B-independent function as well (24,25).…”
mentioning
confidence: 99%
“…The role for LUBAC as a crucial regulator of signalling was discovered in the TNFR1 pathway and it is also the pathway in which its function is best characterised and understood. During the past years, however, LUBAC has also been found to be a decisive factor in many additional immune receptor signalling pathways that involve ubiquitination, including those triggered by Toll-like receptors (TLRs) [for example, liposaccharide (LPS)-activated TLR4 and double-stranded RNA (dsRNA)-activated TLR3 (Emmerich et al, 2013;Ikeda et al, 2011;Zak et al, 2011;Zinngrebe et al, 2016)], interleukin 1 (IL-1) (Emmerich et al, 2013;Gerlach et al, 2011;Ikeda et al, 2011;Tokunaga et al, 2009), retinoic acid-inducible gene-I (RIG-I) and RIG-I-like receptors (RLR) (Belgnaoui et al, 2012;Inn et al, 2011;Liu et al, 2013), a muramyl dipeptide (MDP)activated nucleotide-binding oligomerisation domain (NOD) (Damgaard et al, 2012;Draber et al, 2015;Fiil et al, 2013;Kupka et al, 2016a;Warner et al, 2013), cluster of differentiation 40 (CD40) (Dubois et al, 2014;Gerlach et al, 2011;Hostager et al, 2011), the TNF-related apoptosis-inducing ligand (TRAIL) (Lafont et al, 2017), inflammasomes (Douglas et al, 2015;Gurung et al, 2015;Nastase et al, 2016;Rodgers et al, 2014), CD95 (Taraborrelli et al, 2018) and, last but not least, the Tcell receptor (TCR) (Dubois et al, 2014;Redecke et al, 2016;Yang et al, 2016) (see poster). Together, these studies have established LUBAC and its linear ubiquitin-chain-forming activity as decisive for keeping the physiological balance between gene activation and cell death in immune receptor signalling and, thereby, as crucial regulators of innate and adaptive immunity.…”
Section: Box 2 Lubac In Other Immune Signalling Pathwaysmentioning
confidence: 99%
“…The chromosomal translocation t(14;19)(q32;12) which juxtaposes BCL3 with the IGH locus has been reported to result in an enhanced expression of BCL3 in a variety of lymphoid cancers, such as CLL and less commonly follicular lymphoma as well as marginal-zone lymphoma ( Figure 6c) [226][227][228]. Additionally, amplification as well as alterations in the epigenetic modification status of the BCL3 locus have been observed in HL and anaplastic large cell lymphomas [229][230][231].…”
Section: Atypical Iκb Proteinsmentioning
confidence: 99%
“…Indeed, whereas LUBAC is necessary for TCR signaling, the catalytic activity of HOIP subunit is not required [225], suggesting a scaffold function of LUBAC maybe in relation with TRAF6. However, M1-linked polyubiquitination of Bcl10 has been observed following TCR stimulation [226] and during chronic B cell activation [227] suggesting the specific requirement of LUBAC-dependent linkage of M1 chains. A possible explanation for the observations of Dubois et al [225] would be that quantitative evaluation of TCR/BCR signal transduction upon abolished E3 ligase activity of LUBAC is complicated by the remaining K63-linked dependent activation.…”
Section: The Tcr/bcr Pathwaymentioning
confidence: 99%